2012
DOI: 10.2478/s13382-012-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Subjective complaints of people living near mobile phone base stations in Poland

Abstract: Objectives: The aim of our study was to assess the health conditions and subjective symptoms of the inhabitants living in the base stations vicinity and to analyse the relationship between the complaints and level of exposure to electromagnetic fields (EMF). Materials and Methods: Our study was performed in housing estates located in five regions of Łódź. The electric field measurements were performed in the buildings located closest to the azimuth of the antennas. Respondents were selected by trained intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 13 publications
1
13
0
4
Order By: Relevance
“…Exposure was associated with discomfort, irritability, appetite loss, fatigue, headache, difficulties concentrating, and sleep disturbance. Previous studies have reported that the most exposed people had a higher incidence of fatigue, irritability, headaches, nausea, loss of appetite, sleeping disorders, depression, discomfort, difficulties concentrating, memory loss, visual disorders, dizziness, and cardiovascular problems that are almost similar with our findings [22][23][24][25][26]. However, most of these population based studies did not show statistically significant association of the physical symptoms reported with exposure to BTS and the adverse effects might be due to nocebo effect.…”
Section: Discussionsupporting
confidence: 82%
“…Exposure was associated with discomfort, irritability, appetite loss, fatigue, headache, difficulties concentrating, and sleep disturbance. Previous studies have reported that the most exposed people had a higher incidence of fatigue, irritability, headaches, nausea, loss of appetite, sleeping disorders, depression, discomfort, difficulties concentrating, memory loss, visual disorders, dizziness, and cardiovascular problems that are almost similar with our findings [22][23][24][25][26]. However, most of these population based studies did not show statistically significant association of the physical symptoms reported with exposure to BTS and the adverse effects might be due to nocebo effect.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, it is reasonable to expect that the mechanism of biological activity of EMF emitted by transmitting antennas of base stations and mobile TV transmitters may be similar. This could explain subjective symptoms from the central nervous system (such as headache and dizziness) reported by the residents of areas surrounding base stations, observed by different authors [23,24,[31][32][33][34][35][36][37] where EMF with similar values prevail.…”
Section: Discussionmentioning
confidence: 96%
“…However, the nature of most of the reported subjective symptoms implies their association with impaired neurovegetative regulation of the cardiovascular function [23,24]. In the experimental study by Mann and Roschke, the HRV analysis did not reveal any pathologies in the subjects exposed to pulse-modulated 900 MHz EMF [25].…”
Section: Discussionmentioning
confidence: 97%
“…Navarro et al 8 indicated an association between exposure and depressive symptoms in the population 150m from the mobile phone base stations. Likewise, Bortkievicz et al 9 , Abdel-Rassoul et al 10 , and Hutter et al 30 found more neurobehavioral effects in populations living near the mobile phone base stations when compared to those living more than 300m or 400m from the mobile phone base stations. Eger et al 16 found that five years or more after installation and operation of the mobile phone base stations, the risk of developing cancer tripled for residents within less than 400m from the source, the main beam of which touched the ground at a horizontal distance of 350m.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased libido was the most common complaint in men. According to Navarro et al 8 and Bortkiewicz et al 9 , individuals living close to the mobile phone base stations reported circulatory problems, sleep disorders, irritability, depression, blurred vision, and difficulties in concentrating. Meanwhile, Abdel-Rassoul et al 10 suggested a relationship between living near a mobile phone bases station and neurobehavioral problems like depressive tendency, tremors, dizziness, headache, sleep disorders, and visual disorders, among others.…”
Section: Introductionmentioning
confidence: 99%